How Do MRI Findings Influence Rectal Cancer Management? - Ayloor Seshadri Ramakrishnan; Jeyakumar Pradeep (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Treatment of rectal cancer is currently guided by the need to reduce local recurrence, improve survival, reduce treatment-related toxicity, and improve the patient's quality of life (QoL). Magnetic resonance imaging (MRI) scan is now the imaging modality of choice for rectal cancer. However, the role of MRI in rectal cancer has transformed beyond describing the local stage of cancer to becoming a tool to predict the prognosis of a patient by its ability to detect features associated with a high risk of recurrence and poor survival. This greatly helps the multidisciplinary team (MDT) responsible for treating patients with rectal cancer to stratify them based on the potential for recurrence and decide on the need for and type of preoperative treatment to be offered. MRI also has the ability to assess the response to such treatments, based on which the MDT can tailor the subsequent treatment. This has the potential to spare the patient from unnecessary treatment, thus improving the QoL. MRI provides a roadmap to the surgeon while planning the surgery. In this review, we give a brief overview of the current management strategies for rectal cancer and highlight the role of MRI in the decision-making process.